Acylglycerol Kinase-Targeted Therapies in Oncology - Chu, Binxiang; Hong, Zhenghua; Zheng, Xiaohe (Frontiers in Cell and Developmental Biology, 2021)
Acylglycerol kinase(AGK) is a recently discovered mitochondrial lipid kinase, and mutation of its gene is the fundamental cause of Sengers syndrome. AGK is not only involved in the stability of lipid metabolism but is also closely related to mitochondrial protein transport, glycolysis, and thrombocytopoiesis. Evidence indicates that AGK is an important factor in the occurrence and development of tumors. Specifically, AGK has been identified as an oncogene that partakes in the regulation of tumor cell growth, invasion, metastasis, and drug resistance. The versatility of AGK and its unique role in different types of cancerous and normal cells greatly piqued our interest. We believe that AGK is a promising target for cancer therapy. Therefore, this review summarizes the main research advances concerning AGK, including the discovery of its physiological/pathogenic mechanisms, and provides a reference for the feasible evaluation of AGK as a therapeutic target for human diseases, particularly tumors.